2021
DOI: 10.1186/s12943-021-01418-3
|View full text |Cite
|
Sign up to set email alerts
|

MG53 suppresses tumor progression and stress granule formation by modulating G3BP2 activity in non-small cell lung cancer

Abstract: Background Cancer cells develop resistance to chemotherapeutic intervention by excessive formation of stress granules (SGs), which are modulated by an oncogenic protein G3BP2. Selective control of G3BP2/SG signaling is a potential means to treat non-small cell lung cancer (NSCLC). Methods Co-immunoprecipitation was conducted to identify the interaction of MG53 and G3BP2. Immunohistochemistry and live cell imaging were performed to visualize the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 81 publications
1
35
0
Order By: Relevance
“…Although emerging evidence has improved our understanding of TRIM72 function and its diagnostic and prognostic value in human cancers, the mechanisms involving TRIM72 and cancer development remain poorly understood. Recent studies have unraveled that reduced TRIM72 expression is implicated in a variety of cancer types and cancer-related processes, including proliferation, invasion, and prognosis [ 25 28 ]. Here, we demonstrated that TRIM72 expression was reduced in BC tissues and cell lines; and overexpression of TRIM72 suppressed tumor progression both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although emerging evidence has improved our understanding of TRIM72 function and its diagnostic and prognostic value in human cancers, the mechanisms involving TRIM72 and cancer development remain poorly understood. Recent studies have unraveled that reduced TRIM72 expression is implicated in a variety of cancer types and cancer-related processes, including proliferation, invasion, and prognosis [ 25 28 ]. Here, we demonstrated that TRIM72 expression was reduced in BC tissues and cell lines; and overexpression of TRIM72 suppressed tumor progression both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A deteriorating TME accompanies the increased expression of transcription factors to regulate metabolism, proliferation, and inflammation [ 36 ]. Recently, treatment with the recombinant human MG53 (TRIM72) could inhibit lung cancer tumor growth by blocking ATO-induced SG formation, suggesting that TRIM72 is a key mediator of cancer cells exposed to adverse environments [ 28 ]. Despite the stress-related repressor of TRIM72 having been implicated by previous studies [ 23 , 24 ], the role of TRIM72 in TME-induced pressure and the molecular mechanisms is not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress granules are mRNPs stalled in translation initiation ( 72 ). Targeting these structures has been proven to be a feasible therapy for NSCLC based on a recent study ( 73 ). Our finding suggests that it might be effective to target pre-invasive lesions when it is still characterized by GGO.…”
Section: Discussionmentioning
confidence: 99%
“…SGs are involved in posttranscriptional regulation and translational control. SGs have been found in a variety of tumors and are thought to improve the tolerance of tumor cells to stress stimuli and chemotherapeutic agents ( Grabocka and Bar-Sagi, 2016 ; Li et al, 2021 ). SGs may be related to the formation of the P-body because a certain proportion of RNA-binding proteins (RBPs) and mRNAs shared by SGs and PBs have been found to shuttle between the two when the SG assembly is induced ( Kedersha et al, 2005 ; Moon et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%